A review of concrete 3D printed structural members - Raphael, Benny; Senthilnathan, Shanmugaraj; Patel, Abhishek; Bhat, Saqib (Frontiers in Built Environment, 2023)
Concrete 3D Printing (3DP) is being seen as a potential technology for increasing automation and introducing digital fabrication in the construction industry. Concrete 3DP provides significant advantage over conventional or precast methods, such as the prospects of structurally optimized designs and integrating functional components within the structural volume of the building components. Many previous studies have compiled the state-of-art in this area related to mix properties, lateral stability, support requirements, fiber reinforcement, and continuous reinforcement in the 3D printed elements. However, there are no reviews on the use of concrete 3DP for fabricating structural elements and systems. This paper reviews the work on the digital fabrication of the reinforced structural elements. A systematic literature review process is adopted in which publications are analysed to answer a set of well-defined research questions. The review is structured by grouping the publications into categories based on issues that are addressed and the technology solutions that are proposed. It is concluded that research in this area is still in nascent stage and more studies are needed to adopt 3D printing technology in large-scale construction projects.